Le conservatoire Virt.Os (Virtothèque ostéologique) de Bordeaux - Hélène Coqueugniot; Antony Colombo; Olivier Dutour; Bruno Dutailly (Les Nouvelles de l’Archéologie, 2020)
The VIRT.OS project, funded by the Aquitaine Regional Council, has permitted the creation of a virtual bone library. Its purpose is to assist disciplines concerned with osteological studies such as biological anthropology, archaeozoology, paleontology, anatomy and paleopathology. The specimens, contained in this virtual bone library, originate from different skeletal and osteoarchaeological collections, are digitized by CT scanner, lasergrammetry or photogrammetry. Its objective is to facilitate access to osteological pieces of specific interest, scientific or heritage, while ensuring their preservation. The database, which is continuously enriched, is stored on a dedicated platform hosted by the Huma-Num infrastructure. The 3D osteological models presented on the VIRT.OS website are available for research and teaching or heritage promotion, for researchers working on ancient and modern bones, both animal and human, teachers and the general public.